Present Status of Medicinal Plants for the Management of Vadha Diseases in Northern Province - Pelastina, A.; Sathiyaseelan, V.; Athavan, V. (Institute of Indigenous Medicine University of Colombo, Rajagiriya Sri Lanka, 2017)
Indigenous system of medicine consists of Ayurvedic, Siddha, Unani and traditional medicine. Medicinal plants play an important role to cure major and minor ailments of diseases. Medicinal plants are the backbone of Siddha medicine. Globally, there is a demand to utilize the medicinal plants to manage the acute and chronic diseases. My objective of the study is the present status of medicinal plants for the management of Vadha disease in Northern Province. The research was carried out from June 2016 to February 2017 and other data were collected from the records of department of Gunapapadam for the identification of medicinal plants. Area map was used to identify the medicinal plants. Frequent field visits were made to the areas. Among the identified medicinal plants, 116 medicinal plants were used for Vadha diseases. Identified medicinal plants are classified based on different categories. According to the pharmacological actions, commonly anti-inflammatory, diuretic, deobstruent, anti spasmodic are used among 116 plants. Out of 116 plants, according to the habit, shrubs- 22.41%, trees-31.03%, climbers-9.5%, herbs-37.06%. Out of 116 medicinal plants, based on part used, root-29.31%, leaves-13.79%, whole plant-10.34%, flower-0.86%, rhizome- 6.89%, seeds-7.75%, bark-16.37%, resin-1.72%, latex-16.37%. And 2.58% medicinal plants were given internally, externally-38.79%, internally and externally-35.34%. Based on the life span, annual-35.34%, bineal-21.55%, perineal-45.68%. In these plants, 24 varieties of species are used as food supplements. The public should be encouraged to use these medicinal plants, which don't have any adverse effects, they could be taken as food supplements or simple remedies to manage the Vadha diseases and live a healthy life.
Keywords: Vadha diseases; Northern province; Medicinal plants; Siddha medicine